BLINATUMOMAB IN THE THERAPY OF ACUTE B-LYMPHOID LEUKEMIA - Ugo Testa; Elvira Pelosi; Germana Castelli; Patrizia Chiusolo (Mediterranean Journal of Hematology and Infectious Diseases)
Blinatumomab, a CD19-CD3 bispecific T cell engager (BiTE), has two recombinant single-chain variable fragments that temporarily link CD3+ T cells and CD19+ B cells, leading to the T cell-mediated lysis of neoplastic B cells. Improved minimal residual disease (MRD)-negative response rates and long-term overall survival have been observed in B-ALL patients who received this drug. These therapeutic successes have led to FDA approval for refractory/relapsed and MRD-positive B-ALL patients. Furthermore, recent studies in newly diagnosed B-ALL patients have led in Philadelphia chromosome-positive patients to the development of chemotherapy-free regimens based on tyrosine kinase inhibitors plus Blinatumomab and in Philadelphia chromosome-negative patients to improvement in outcomes using chemotherapy regimens that have incorporated Blinatumomab in the consolidation phase of treatment.